2006
DOI: 10.1089/aid.2006.22.1236
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Factors Associated with Hepatocellular Carcinoma among Hepatitis C Virus and Human Immunodeficiency Virus Coinfected Patients with Decompensated Cirrhosis

Abstract: We compared the incidence of and factors associated with hepatocellular carcinoma (HCC) among hepatitis C virus (HCV)-monoinfected subjects and human immunodeficiency virus (HIV)/HCV-coinfected individuals, both with decompensated cirrhosis. In a retrospective study, a cohort of 180 individuals with HIV coinfection and 1037 HCV-monoinfected patients with decompensated HCV-related cirrhosis from eight centres in Spain were analyzed. HCC was found in 234 (23%) HCV-monoinfected subjects and in four (2%) HIV-coinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The low incidence of HCC is probably due to the fact that the length of HCV infection in the patients included in this study is still short, so that HCC, a late complication of HCV-related chronic liver disease, has little chance to emerge. 31 As the follow-up of these patients increases, likely the incidence of HCC becomes greater. Higher frequencies of consumption of depressors of central nervous system and of bacterial infections have been proposed as possible causes of the greater incidence of HE in coinfected patients compared with that found in HCV-monoinfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The low incidence of HCC is probably due to the fact that the length of HCV infection in the patients included in this study is still short, so that HCC, a late complication of HCV-related chronic liver disease, has little chance to emerge. 31 As the follow-up of these patients increases, likely the incidence of HCC becomes greater. Higher frequencies of consumption of depressors of central nervous system and of bacterial infections have been proposed as possible causes of the greater incidence of HE in coinfected patients compared with that found in HCV-monoinfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection itself has not been associated with an increased risk of HCC [57, 58]. A PubMed literature search for HIV infection and HCC yielded few studies from the US and Europe that looked at the effect of HIV infection on the incidence, characteristics and progression of HCC (summarized in Table 1).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…It has also been reported that in HIV/HCV-coinfected patients, HIV may promote the development of cirrhosis 10 to 20-fold, and that of HCC five-fold [33]. Some authors have compared the incidence of HCC in HIV/HCV-coinfected patients with that seen in HCVmonoinfected patients in large, retrospective cohorts, and they described a still higher incidence of HCC among HCV-monoinfected patients than in HIV/HCV-coinfected patients, mainly due to the longer duration of HCV infection in the monoinfected group [34,35]. However, Ioannou et al [6] reported a greater progression in the prevalence of cirrhosis and HCC in the HIV/HCV population (3.7-fold for cirrhosis and 23-fold for HCC) than among HCV-monoinfected patients, because of the accelerated course of liver disease in the former group.…”
Section: Epidemiology Of Hepatocellular Carcinoma In Hiv Patientsmentioning
confidence: 99%